Thalidomide prevents antibody-mediated immune thrombocytopenia in mice. Issue 183 (November 2019) - Xu, Mengdi; Wang, Xiamin; Xu, Xiaoqi; Wei, Guangyu; Lu, Wenyi; Luo, Qi; Li, Xiaoqian; Liu, Yun; Ju, Wen; Li, Zhenyu; Xu, Kailin; Zeng, Lingyu; et al.
Abstract: Immune thrombocytopenia (ITP) is a heterogeneous autoimmune disorder characterized by immune-mediated platelet destruction, leading to lower platelet count. Thalidomide is considered as a novel immunomodulatory drug for treating several autoimmune diseases. Whether thalidomide can ameliorate ITP remains unclear. This study aims to evaluate the effect of thalidomide on ITP mouse model. ITP mouse model was established through intraperitoneal injection of rat anti-mouse integrin GPIIb/CD41 immunoglobulin. Thalidomide (10, 20 or 50 mg/kg body weight) was intraperitoneally injected into mice followed by antibody injection. Then, peripheral blood and plasma was isolated for analysis of platelet count and the level of IFN-γ and IL-17 in plasma. Meanwhile, spleen was extracted to measure the expression of CD68, a macrophage marker. In addition, macrophage cell line RAW264.7 was cultured and treated with thalidomide followed by analysis of cell viability, apoptosis as well as cell cycle. Thalidomide prevented antiplatelet antibody-mediated platelet destruction in ITP mouse model. Compared with vehicle (phosphate-buffered saline), thalidomide significantly inhibited the secretion of IFN-γ and IL-17 in ITP mouse and reduced the expression of CD68 in spleen. After thalidomide treatment, the cell viability of RAW264.7 cell was significantly reduced and the cell number in S phase was also significantly decreased. In addition, the expression of cyclin E2 was significantly reduced. In conclusion, thalidomide prevents antiplatelet antibody-mediated platelet destruction in ITP mouse possibly through reducing the number of macrophages, suggesting that it might be a novel approach for treating ITP. Highlights: Thalidomide prevented antibody-mediated platelet destruction in ITP mice. Thalidomide reduced level of IFN-γ, IL-17 and CD68 in ITP mice. Thalidomide reduced RAW264.7 cell viability and cell numbers in S phase. Thalidomide decreased cyclin E2 expression.